Effect of 5Hz electromagnetic waves on movement behavior in male wistar rats (in vitro) - Mahdavi, Seyed Mohammad; Sahraei, Hedayat; Tavakoli, Hassan; Yaghmaei, Paricher (Archives of Advances in Biosciences, 2013)
Various stresses during life can affect metabolism and brain activities, immune and endocrine systems directly and indirectly, and ultimately, causes animal behavior change. The cellular and molecular level change in neurotransmitter and hormone concentrations led to the functional changes of operating systems in the intracellular organelles. These events cause of course oxidative stress. All these reactions cause general or limited inflammation that is characterized by increased phenomena of inflammatory cytokines. Electromagnetic waves are the most important stimulus of ions and biomolecules therefore they change ions movement in a living organism. This process can lead to neuronal and behavioral changes. Yet, certainly, radiation pattern, intensity and magnetic field strength will be highly effective in response (reaction). In the present study, short-term (one day) and medium-term (3 days and 7days) and long-term (19 days and 21 days) effects of extremely low-frequency waves (ELF) on behavioral and metabolic activities in male wistar rats with an average weight 180-250g have been investigated.